Relationship between Human Resource Management Practices and Employee’s Turnover Intention: An Empirical Study (Sains Humanika, 2021)
The objective of this study was to identify the relationship between Human Resource Management (HRM) practices and employees’ turnover intention. This study employed a quantitative research approach by conducting a survey to collect data. By using convenience sampling, 70 permanent employees from the organization were sampled for the study. Employing SPSS version 18.0, descriptive statistical analysis revealed that level of HRM practices was moderate while turnover intention of respondents was at low level. Meanwhile, Spearman's rank correlation coefficient analysis showed that HRM practices were significantly negative correlated with turnover intention. In conclusion, these findings can be used by the management board of the organization to understand their employees’ turnover intention and further improve HRM practices.
Keywords: Human resource management practices, turnover intention, hospitality industry, performance appraisal and reward